The design, fabrication, and photocatalytic utility of nanostructured semiconductors: focus on TiO2-based nanostructures - Arghya Narayan Banerjee (Dove Medical Press, 2011)
Arghya Narayan BanerjeeSchool of Mechanical Engineering, Yeungnam University, Gyeongsan, South KoreaAbstract: Recent advances in basic fabrication techniques of TiO2-based nanomaterials such as nanoparticles, nanowires, nanoplatelets, and both physical- and solution-based techniques have been adopted by various research groups around the world. Our research focus has been mainly on various deposition parameters used for fabricating nanostructured materials, including TiO2-organic/inorganic nanocomposite materials. Technically, TiO2 shows relatively high reactivity under ultraviolet light, the energy of which exceeds the band gap of TiO2. The development of photocatalysts exhibiting high reactivity under visible light allows the main part of the solar spectrum to be used. Visible light-activated TiO2 could be prepared by doping or sensitizing. As far as doping of TiO2 is concerned, in obtaining tailored material with improved properties, metal and nonmetal doping has been performed in the context of improved photoactivity. Nonmetal doping seems to be more promising than metal doping. TiO2 represents an effective photocatalyst for water and air purification and for self-cleaning surfaces. Additionally, it can be used as an antibacterial agent because of its strong oxidation activity and superhydrophilicity. Therefore, applications of TiO2 in terms of photocatalytic activities are discussed here. The basic mechanisms of the photoactivities of TiO2 and nanostructures are considered alongside band structure engineering and surface modification in nanostructured TiO2 in the context of doping. The article reviews the basic structural, optical, and electrical properties of TiO2, followed by detailed fabrication techniques of 0-, 1-, and quasi-2-dimensional TiO2 nanomaterials. Applications and future directions of nanostructured TiO2 are considered in the context of various photoinduced phenomena such as hydrogen production, electricity generation via dye-sensitized solar cells, photokilling and self-cleaning effect, photo-oxidation of organic pollutant, wastewater management, and organic synthesis.Keywords: TiO2 nanostructure, fabrication techniques, doping in TiO2, TiO2-assisted photoactivity, solar hydrogen, TiO2-based dye-sensitized solar cells, TiO2 self-cleaning, organic synthesis